Gumption : relighting the torch of freedom with America's gutsiest troublemakers - Offerman, Nick, 1970- (Dutton, 2015)
The star of Parks and Recreation and author of the best-selling Paddle Your Own Canoe pays tribute to inspiring mischief makers, from George Washington to Willie Nelson, while expounding on such topics as religion, handcrafting and meat.